Phosphate positive electrode material and preparation method thereof, positive electrode plate and secondary battery

By doping metal elements into the core of the sodium vanadium fluorophosphate positive electrode material and covering the carbon layer, the problems of poor electron conductivity and insufficient structural stability of traditional phosphate positive electrode materials are solved, and high energy density and excellent electrochemical properties are achieved.

CN119812313APending Publication Date: 2025-04-11HUBEI WANRUN NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510096123.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional phosphate cathode materials have defects such as poor electron conductivity, low compaction density and small specific surface area of ​​BET, which limit their performance in electrochemical properties.

Method used

Sodium vanadium fluorophosphate material doped with metal elements such as Fe, Mn, Ti, Al and Mg is used as the core, and a carbon layer is coated on the core. The structural stability and electrochemical performance are improved through two-step sintering treatment.

Benefits of technology

The electron conductivity, structural stability and energy density of the phosphate positive electrode material are significantly improved, making it excellent in capacity, rate performance and cycle performance, and obtaining a high-energy-density sodium ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812313A_ABST
    Figure CN119812313A_ABST
Patent Text Reader

Abstract

The invention provides a phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery, and belongs to the field of battery materials, and the phosphate positive electrode material comprises an inner core and a carbon layer coating the inner core; the expression of the inner core is Na3V2-x-yAxBy (PO4) 2F3; wherein 0 < = x < = 0.5, 0 < = y < = 0.5, and x and y are not zero at the same time; the element A and the element B independently comprise one or more of Fe, Mn, Ti, Al and Mg, and the element A and the element B are different from each other; the compaction density of the phosphate positive electrode material is greater than or equal to 2.0 g / cm < 3 >, and the BET specific surface area is greater than or equal to 8m < The inner core of the phosphate positive electrode material is doped with a high-voltage platform metal element, and the inner core is coated with a carbon layer, so that the electron conductivity, the compaction density and the BET specific surface area of the phosphate positive electrode material are effectively improved, and the phosphate positive electrode material is excellent in capacity, rate capability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] Sodium-ion Battery (SIB) is a kind of battery that relies on sodium ions (Na + ) is a secondary battery that moves between the positive and negative electrodes to achieve charge and discharge. Its working principle is similar to that of the mainstream secondary battery lithium-ion battery (LIB). It has attracted much attention due to its advantages such as abundant sodium ion resources in the earth's crust and low price. It has become the most likely substitute for LIB in grid-scale energy storage and power batteries for new energy vehicles. Among the positive electrode materials of sodium ion batteries, polyanionic compounds (PAC) have very excellent cycle life and have very broad application prospects in the field of SIB.

[0003] Sodium Super Ionic Conductor (NASICON) is one of the representative PAC materials. It has a stable three-dimensional open framework and can realize Na + Phosphate materials, such as sodium vanadium phosphate (Na3V2(PO4)3, NVP) and sodium vanadium fluorophosphate (Na3V2(PO4)2F3, NVPF), are typical NASICON materials and can be used as positive electrode materials for SIBs. However, traditional phosphate positive electrode materials have defects such as poor electronic conductivity, low compaction density and small BET specific surface area, which limit their electrochemical performance. Summary of the invention

[0004] In view of the technical problems existing in the background technology, the present application provides a phosphate positive electrode material and its preparation method, a positive electrode plate and a secondary battery, aiming to solve the technical problems that traditional phosphate positive electrode materials have defects such as poor electronic conductivity, low compaction density and small BET specific surface area, which limit their electrochemical performance.

[0005] In a first aspect, an embodiment of the present application provides a phosphate positive electrode material, comprising a core and a carbon layer covering the core;

[0006] The kernel expression is Na 3+x+y V 2-x-y A x B y (PO4)2F3;

[0007] Among them, 0≤x≤0.5, 0≤y≤0.5, x and y are not zero at the same time;

[0008] The A element and the B element each independently include one or more of Fe, Mn, Ti, Al and Mg, and the A element and the B element are different from each other;

[0009] The compaction density of phosphate cathode material is ≥2.0g / cm 3 , BET specific surface area ≥8m 2 / g.

[0010] In the technical solution of the embodiment of the present application, the core of the phosphate positive electrode material is a sodium vanadium fluorophosphate material doped with at least one of element A and element B. Element A and element B are selected from metal elements such as Fe, Mn, Ti, Al and Mg that are beneficial to improving the voltage platform, which helps to optimize the electronic conductivity of the phosphate positive electrode material and effectively improve the average voltage platform. At the same time, the compaction density and BET specific surface area of ​​the phosphate positive electrode material are controlled, and a carbon layer is coated on the core to further improve the electronic conductivity, structural stability and energy density of the phosphate positive electrode material, which is beneficial to the phosphate positive electrode material to perform well in capacity, rate performance and cycle performance, thereby obtaining a high energy density sodium ion battery.

[0011] In some embodiments, the mass fraction of the carbon layer in the phosphate positive electrode material is 1.8% to 3%; and / or the thickness of the carbon layer is 0.8 nm to 1.8 nm.

[0012] In this embodiment, controlling the mass fraction and / or thickness of the carbon layer within the above range is beneficial to ensuring that the carbon layer has a good coating effect on the inner core, and has the effects of improving electronic conductivity, enhancing structural stability, and inhibiting the occurrence of side reactions, thereby improving the electrochemical properties of the phosphate positive electrode material, such as specific capacity, rate performance, and cycle performance.

[0013] In some embodiments, the first charge specific capacity of the phosphate cathode material at 0.1C is ≥120 mAh / g.

[0014] In some embodiments, the first discharge specific capacity of the phosphate positive electrode material at 0.1C is ≥110 mAh / g.

[0015] In some embodiments, the first coulombic efficiency of the phosphate cathode material at 0.1C is ≥90%.

[0016] In this embodiment, the phosphate positive electrode material has a high charge specific capacity, discharge specific capacity and first coulombic efficiency, thereby ensuring that the positive electrode plate and the secondary battery have the advantages of high specific capacity and good rate performance.

[0017] In a second aspect, the present application provides a method for preparing a phosphate positive electrode material, comprising the following steps:

[0018] A vanadium source, oxalic acid, a phosphorus source, a dopant and a solvent are mixed and subjected to a reaction treatment to obtain a mixed solution;

[0019] The mixed liquid is subjected to a first drying process and a first sintering process to obtain a precursor;

[0020] The precursor, the sodium source, the fluorine source and the carbon source are mixed and ground to obtain a slurry;

[0021] The slurry is subjected to a second drying process and a second sintering process to obtain the phosphate positive electrode material;

[0022] The dopant includes a first source and / or a second source, the first metal element in the first source and the second metal element in the second source each independently include one or more of Fe, Mn, Ti, Al and Mg, and the first metal element and the second metal element are different from each other.

[0023] In the technical solution of the embodiment of the present application, by performing a two-step sintering treatment, the first metal element and / or the second metal element in the dopant are more easily embedded in the crystal structure of the sodium vanadium fluorophosphate material, thereby improving the structural stability of the phosphate positive electrode material, and the first metal element and / or the second metal element are conducive to promoting the phosphate positive electrode material to melt more completely during the high-temperature sintering process, making the surface morphology more dense and smooth, thereby improving the compaction density, BET specific surface area, rate performance, and cycle performance of the phosphate positive electrode material. At the same time, the introduction of reducing oxalic acid in the preparation process of the precursor is conducive to the reduction of the vanadium element in the vanadium source, and the oxalic acid has almost no residual carbon after the sintering treatment, which is conducive to better controlling the carbon content and surface morphology of the phosphate positive electrode material, and improving the compaction density and BET specific surface area of ​​the phosphate positive electrode material. Therefore, the phosphate positive electrode material prepared in the embodiment of the present application not only has a significantly improved compaction density and BET specific surface area, but also a carbon layer is coated on the inner core of the phosphate positive electrode material, which further improves the electronic conductivity, structural stability and energy density of the phosphate positive electrode material, thereby ensuring its excellent performance in specific capacity, rate performance and cycle performance, which is conducive to the preparation of high energy density sodium ion batteries.

[0024] In some embodiments, the step of mixing a vanadium source, oxalic acid, a phosphorus source, a dopant and a solvent, and subjecting the mixture to a reaction treatment to obtain a mixed solution comprises:

[0025] The vanadium source and the solvent are mixed at a first temperature for a first time to obtain a first solution;

[0026] The first solution, the dopant and the oxalic acid are mixed at a second temperature for a second time to obtain a second solution;

[0027] The second solution and the phosphorus source are mixed at a third temperature for a third time to obtain the mixed solution;

[0028] Wherein, the first temperature is 80°C to 90°C, and the first time is 30min to 90min;

[0029] The second temperature is 90°C to 95°C, and the second time is 30min to 60min;

[0030] The third temperature is 90° C. to 100° C., and the third time is 12 min to 36 min.

[0031] In this embodiment, the first solution containing the vanadium source is used as the reaction base solution, and the dopant, oxalic acid and phosphorus source are gradually added to react. This is beneficial to ensure that the raw materials are mixed evenly and react fully, and makes it easier for the metal elements in the dopant to be embedded in the crystal structure of the precursor, which is beneficial to improve the purity and structural stability of the phosphate positive electrode material.

[0032] In some embodiments, when the dopant includes the first source and the second source, the ratio of the amount of vanadium element in the vanadium source, the oxalic acid, the phosphorus element in the phosphorus source, the first metal element in the first source and the second metal element in the second source is (0.9~1.1):(2.5~3.5):1:(0~0.25):(0~0.25).

[0033] In this embodiment, by controlling the amount ratio of each element in the raw material, it is beneficial to fully react between the raw materials to obtain a high-purity precursor.

[0034] In some embodiments, the vanadium source includes one or more of vanadium pentoxide, vanadium trioxide, vanadium dioxide, ammonium metavanadate, sodium metavanadate, sodium orthovanadate, and vanadyl oxalate.

[0035] In some embodiments, the phosphorus source includes one or more of phosphoric acid, diammonium phosphate, monoammonium phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.

[0036] In some embodiments, the first source includes one or more of oxides, hydroxides, and salt compounds containing the first metal element.

[0037] In some embodiments, the second source includes one or more of oxides, hydroxides, and salt compounds containing the second metal element.

[0038] In some embodiments, the molar ratio of the phosphorus element in the precursor, the sodium element in the sodium source, the fluorine element in the fluorine source, and the carbon element in the carbon source is 1:(1.3-1.5):(1.3-1.5):(0.48-0.9).

[0039] In this embodiment, by controlling the molar ratio of each element in the raw materials, the raw materials are fully reacted to form a high-purity sodium vanadium fluorophosphate material, and a carbon layer with a moderate thickness and carbon content is coated on its surface.

[0040] In some embodiments, the sodium source includes one or more of sodium fluoride, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and sodium phosphate.

[0041] In some embodiments, the fluorine source includes one or more of sodium fluoride, ammonium fluoride, and hydrogen fluoride.

[0042] In some embodiments, the carbon source comprises one or more of glucose, polyethylene glycol, sucrose, and ascorbic acid.

[0043] In this embodiment, the selection of different carbon sources is beneficial to adjusting the compaction density, BET specific surface area and electrochemical performance of the phosphate positive electrode material, thereby improving the comprehensive performance of the phosphate positive electrode material.

[0044] In some embodiments, the sintering temperature of the first sintering treatment is 700° C. to 750° C., and the holding time is 1 h to 3 h.

[0045] In this embodiment, the first sintering treatment is carried out at 700° C. to 750° C. for 1 h to 3 h, which is beneficial to improving the crystallinity of the precursor, thereby improving the purity of the phosphate positive electrode material and further improving the electrochemical performance of the phosphate positive electrode material.

[0046] In some embodiments, the sintering temperature of the second sintering treatment is 550° C. to 750° C., and the holding time is 8 h to 12 h.

[0047] In this embodiment, the second sintering treatment is carried out at 550°C to 750°C for 8h to 12h, which effectively controls energy consumption while avoiding the formation of excessive impurities during the sintering process, helping to improve the crystallinity and purity of the phosphate positive electrode material, thereby improving the electrochemical properties such as charge specific capacity and discharge specific capacity.

[0048] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the phosphate positive electrode material provided in the first aspect of the present application, or comprising a phosphate positive electrode material prepared by the preparation method of the phosphate positive electrode material provided in the second aspect of the present application.

[0049] In this embodiment, the positive electrode plate includes the above-mentioned phosphate positive electrode material, and thus has the advantages of high charge specific capacity and discharge specific capacity, good rate performance and excellent cycle performance.

[0050] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode plate provided in the third aspect of the present application.

[0051] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of high charge specific capacity and discharge specific capacity, good rate performance and excellent cycle performance.

[0052] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0054] Figure 1 is a schematic flow chart of a method for preparing a phosphate positive electrode material in an embodiment;

[0055] Figure 2 This is a morphology result diagram of the phosphate positive electrode material of Example 1;

[0056] Figure 3 This is a morphology result diagram of the phosphate positive electrode material of Comparative Example 1;

[0057] Figure 4 The charge and discharge curve diagram of the phosphate positive electrode material of Example 1;

[0058] Figure 5 This is the charge and discharge curve of the phosphate positive electrode material of Comparative Example 1. DETAILED DESCRIPTION

[0059] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0061] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0062] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0063] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0064] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0065] In the description of the embodiments of the present application, unless otherwise specified, the solvent in the "solution" or "base solution", or "water", is at least one of distilled water, deionized water, pure water, and ultrapure water.

[0066] the term

[0067] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:

[0068] Particle size: For spherical particles, the particle size refers to the diameter of the spherical particles. For non-spherical particles, such as particles with an olivine morphology, the particle size usually refers to the equivalent particle size of the non-spherical particles (generally referred to as the particle size), which can be obtained by using a scanning electron microscope (SEM) or a laser particle size analyzer. Among them, the equivalent particle size refers to when a certain physical property of a particle is the same or similar to that of a homogeneous spherical particle, the diameter of the spherical particle is used to represent the diameter of the actual particle. Unless otherwise specified or there is a contradiction, the particle size in this application represents the equivalent particle size.

[0069] Particle size distribution parameters: In the particle size distribution curve of particles, the particle size corresponding to the cumulative particle size distribution percentage reaching N% is called the DN particle size, which means that the particles smaller than this particle size account for N% of all particles, where N = 0 to 100. When N = 100, the D100 particle size indicates the particle size corresponding to the cumulative particle size distribution percentage reaching 100%. When N = 50, the D50 particle size is the particle size corresponding to the cumulative particle size distribution percentage reaching 50%, indicating the median particle size or median diameter, indicating that particles smaller than and larger than this particle size each account for 50%. For example, D50 particle size = 1mm, which means that particles with a particle size smaller than 1mm and particles with a particle size larger than 1mm each account for 50% of all particles.

[0070] The demand for capacity and compaction density of sodium-ion batteries (SIBs) in the commercialization process is getting higher and higher. High capacity and high compaction density mean higher energy density after being assembled into a battery. At present, the electrode materials of SIBs face some huge challenges, such as difficult-to-overcome structural instability, slow ion diffusion, low operating voltage, and low energy / power density. In order to solve these problems, researchers are mainly committed to designing and preparing new electrode materials with high adaptability and reversibility in the process of large sodium ion intercalation / extraction. Transition metal oxides (TMOs) and polyanionic compounds (PACs) with layered structures are the two most promising candidate materials for the positive electrode materials of SIBs. The theoretical capacity of PAC materials is slightly lower than that of TMO materials (such as NaMnO2, P2-Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2 and vanadium oxide, etc.), but PAC materials usually have better cycle life than TMO materials and can meet the requirements of grid-level energy storage for ultra-long cycle life. Therefore, if the comprehensive electrochemical performance of PAC materials (including high-rate capability, specific capacity and operating voltage) is improved, its application prospects in SIBs will be very broad.

[0071] Sodium Super Ionic Conductor (NASICON) is one of the representative PAC materials, in which there is a stable three-dimensional (3D) open framework composed of PO tetrahedrons and MO octahedrons (M represents transition metal), which can realize Na + Rapid migration. Sodium vanadium phosphate (Na3V2(PO4)3, NVP) is the most typical NASICON material with a theoretical capacity of 117.6mAh / g and an operating voltage of 3.3V~3.4V. It can provide a material-based energy density of about 394Wh / kg, which is significantly lower than the theoretical value of phosphate cathode materials in LIBs. Therefore, a major challenge facing phosphate cathode materials used in SIBs is to improve energy density to narrow the gap between theoretical energy density and actual energy density. Compared with NVP without fluorine, NASICON materials doped with fluorine usually have higher operating voltages. For example, sodium vanadium fluorophosphate (Na3V2(PO4)2F3, NVPF) can provide an average operating voltage of up to 3.95V, a theoretical capacity of 128mAh / g, and a corresponding theoretical energy density of up to 507Wh / kg. Therefore, NVPF is a more attractive and promising high-energy-density NASICON material that can be used in SIBs. However, as a member of the NASICON family, NVPF also suffers from the defect of low electronic conductivity, and also has problems such as low compaction density and small BET specific surface area, which limits its capacity and rate performance and prevents it from achieving comprehensive and excellent electrochemical performance including high energy density.

[0072] In order to solve the technical problems that the defects of traditional phosphate positive electrode materials such as poor electronic conductivity, low compaction density and small BET specific surface area limit their electrochemical performance, the present application provides a phosphate positive electrode material and its preparation method, a positive electrode plate and a secondary battery, wherein the core of the phosphate positive electrode material is a sodium vanadium fluorophosphate material doped with metal elements, and a carbon layer is coated on the core, which effectively improves the electronic conductivity, compaction density and BET specific surface area of ​​the phosphate positive electrode material, so that it excels in capacity, rate performance and cycle performance, thereby improving the capacity, rate performance and cycle performance of the positive electrode plate and the secondary battery.

[0073] In a first aspect, an embodiment of the present application provides a phosphate positive electrode material, comprising a core and a carbon layer coating the core;

[0074] The kernel expression is Na 3+x+y V 2-x-y A x B y (PO4)2F3;

[0075] Among them, 0≤x≤0.5, 0≤y≤0.5, x and y are not zero at the same time;

[0076] The A element and the B element each independently include one or more of Fe, Mn, Ti, Al and Mg, and the A element and the B element are different from each other;

[0077] The compaction density of phosphate cathode material is ≥2.0g / cm 3 , BET specific surface area ≥8m 2 / g.

[0078] In the technical solution of the embodiment of the present application, the core of the phosphate positive electrode material is a sodium vanadium fluorophosphate material doped with at least one of element A and element B. Element A and element B are selected from metal elements such as Fe, Mn, Ti, Al and Mg that are beneficial to improving the voltage platform, which helps to optimize the electronic conductivity of the phosphate positive electrode material and effectively improve the average voltage platform. At the same time, the compaction density and BET specific surface area of ​​the phosphate positive electrode material are controlled, and a carbon layer is coated on the core to further improve the electronic conductivity, structural stability and energy density of the phosphate positive electrode material, which is beneficial to the phosphate positive electrode material to perform well in capacity, rate performance and cycle performance, thereby obtaining a high energy density sodium ion battery.

[0079] As an example, the compaction density of phosphate cathode materials is ≥ 2.0 g / cm 3 , including but not limited to 2.0g / cm 3 , 2.02g / cm 3 , 2.04g / cm 3 , 2.06g / cm 3 , 2.08g / cm 3 , 2.1g / cm 3 , 2.12g / cm 3 , 2.14g / cm 3 , 2.16g / cm 3 , 2.18g / cm 3 or 2.2g / cm 3 Furthermore, the compaction density of the phosphate cathode material is preferably 2.03 g / cm 3 ~2.13g / cm 3 The phosphate positive electrode material has a higher compaction density, which is beneficial to improving the specific capacity and rate performance, and is beneficial to reducing the amount of phosphate positive electrode material used and reducing the preparation cost of sodium ion batteries.

[0080] As an example, the BET specific surface area of ​​phosphate cathode materials is ≥ 8 m 2 / g, including but not limited to 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5 m 2 / g, 9.8 m 2 / g, 10 m 2 / g, 12 m 2 / g, 14 m 2 / g, 16 m 2 / g, 18 m 2 / g or 20 m 2 / g. Further, the BET specific surface area of the phosphate cathode material is preferably 10 m 2 / g to 15.5 m 2 / g. The phosphate cathode material has a moderate specific surface area, which is beneficial to providing more active sites for the occurrence of electrochemical reactions and improving the transport rate of sodium ions, helping the sodium-ion battery to have a higher specific capacity and better rate performance.

[0081] It can be understood that the values of x and y independently include but are not limited to 0, 0.01, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5, and x and y are not both zero at the same time. If x = 0 or y = 0, the core of the phosphate cathode material is doped with at least one metal cation. If 0 < x ≤ 0.5 and 0 < y ≤ 0.5, the core of the phosphate cathode material is doped with at least two different metal cations, thus forming a high-entropy doped sodium vanadium fluorophosphate material.

[0082] It can be understood that according to the value ranges of x and y, (2 - x - y):x:y = (1 - 2):(0 - 0.5):(0 - 0.5), and non-limiting examples include but are not limited to: 1:0.5:0.5, 1.1:0.5:0.4, 1.1:0.4:0.5, 1.2:0.4:0.4, 1.3:0.4:0.3, 1.3:0.3:0.4, 1.4:0.3:0.3, 1.5:0.3:0.2, 1.5:0.2:0.3, 1.6:0.2:0.2, 1.7:0.2:0.1, 1.7:0.1:0.2, 1.8:0.1:0.1, 1.9:0.05:0.05, 1.9:0.1:0 or 1.9:0:1.

[0083] It can be understood that the A element and the B element each independently include one or more of Fe, Mn, Ti, Al and Mg, and the A element and the B element are different from each other, and the combination of the A element and the B element includes but is not limited to: Fe and Mn; Fe and Ti; Fe and Al; Fe and Mg; Mn and Ti; Mn and Al; Mn and Mg; Ti and Al; Ti and Mg; Al and Mg; Fe, Mn and Ti; Fe, Mn and Al; Fe, Mn and Mg; Fe, Ti and Al; Fe, Ti and Mg; Fe, Al and Mg; Fe, Mn, Ti and Al; Fe, Mn, Ti and Mg; Fe, Mn, Ti, Al and Mg, etc. When the A element is selected from at least two metal elements, the expression of the inner core can be Na3V 2-x-y A1 x1 A2 x2 A3 x3...... An xn B y (PO4)2F3, wherein A1, A2, A3...An are different metal elements, 0≤x1+x2+x3+...+xn≤0.5. When the B element is selected from at least two metal elements, the expression of the inner core can be Na3V 2-x-y A x B1 y1 B2 y2 B3 y3...... Bm yn (PO4)2F3, where B1, B2, B3...Bm are different metal elements, 0≤y1+y2+y3+...+ym≤0.5. When the A element and the B element are independently selected from two metal elements, the expression of the core can be Na3V 2-x-y A1 x1 A2 x2 B1 y1 B2 y2 (PO4)2F3, wherein A1, A2, B1, B2 are different metal elements, 0≤x1+x2≤0.5, 0≤y1+y2≤0.5.

[0084] In the technical solution of the embodiment of the present application, the ionic radius of metals such as Fe, Mn, Ti, Al and Mg are all similar to V 3+ The ionic radius (0.062nm) is similar, which is conducive to expanding the Na +The diffusion channel of the phosphate cathode material is improved, the ionic conductivity of the phosphate cathode material is improved, and the structural phase change during the charge-discharge process is inhibited, thereby weakening the voltage attenuation caused by the phase change. Compared with NVPF without metal cation doping, the average voltage platform and specific capacity of the phosphate cathode material are effectively improved after doping with metal cations with high voltage platforms such as Fe, Mn, Ti, Al and Mg in the sodium vanadium fluorophosphate material. The co-doping of metal cations of specific types and specific proportions is also conducive to promoting the phosphate cathode material to melt more completely during the high-temperature sintering process, making the surface morphology more dense and smooth, thereby improving the compaction density, BET specific surface area and specific capacity of the sodium vanadium fluorophosphate material.

[0085] In some embodiments, the A element is selected from Fe, and the B element is selected from Ti.

[0086] In this embodiment, the compaction density and BET specific surface area of ​​the phosphate positive electrode material are further improved, so that the specific capacity, rate performance and cycle performance of the phosphate positive electrode material are further improved.

[0087] In some embodiments, 0.05≤x≤0.3, 0.05≤y≤0.3. It can be understood that according to the values ​​of x and y, (2-xy):x:y=(1.4-1.9):(0.05-0.3):(0.05-0.3).

[0088] In this embodiment, controlling the doping ratio of element A and element B within the above range is conducive to obtaining a phosphate positive electrode material with high compaction density, low powder resistivity and high average voltage platform voltage.

[0089] In some embodiments, 0.05≤x≤0.25, 0.05≤y≤0.25. It can be understood that according to the values ​​of x and y, (2-xy):x:y=(1.5-1.9):(0.05-0.25):(0.05-0.25).

[0090] In this embodiment, controlling the doping ratio of element A and element B within the above range is beneficial to obtaining a phosphate positive electrode material with higher compaction density, lower powder resistivity, and higher average voltage platform voltage.

[0091] In some embodiments, 0.1≤x≤0.2, 0.1≤y≤0.2. It can be understood that according to the value range of x and y, (2-xy):x:y=(1.6-1.8):(0.1-0.2):(0.1-0.2).

[0092] In this embodiment, controlling the doping ratio of element A and element B within the above range is more conducive to obtaining a phosphate positive electrode material with higher compaction density, lower powder resistivity, and higher average voltage platform voltage, thereby helping to further improve the electrochemical properties of the phosphate positive electrode material, such as charge specific capacity, discharge specific capacity, first coulombic efficiency, and rate performance.

[0093] In some embodiments, the core of the phosphate cathode material has one or more of the following expressions:

[0094] VtV 1.8 Fe 0.1 Ti 0.1 (PO4)2F3;Na3V 1.7 Fe 0.2 Ti 0.1 (PO4)2F3;Na3V 1.6 Fe 0.2 Ti 0.2 (PO4)2F3;Na3V 1.9 Fe 0.05 Ti 0.05 (PO4)2F3;Na3V 1.4 Fe 0.3 Ti 0.3 (PO4)2F3;Na3V 1.8 Fe 0.1 Mn 0.1 (PO4)2F3;Na3V 1.8 Mn 0.1 Al 0.1 (PO4)2F3;Na3V 1.8 Ti 0.1 Mg 0.1 (PO4)2F3;Na3V 1.9 Fe 0.1 (PO4)2F3;Na3V 1.9 Ti 0.1 (PO4)2F3;Na3V 1.6 (FeAlMnTi) 0.1 (PO4)2F3;Na3V 1.65 Fe 0.1 Ti 0.25 (PO4)2F3;Na3V 1.65 Fe 0.25 Ti 0.1 (PO4)2F3;Na 2.95 V 1.8 Fe 0.1 Ti 0.1 (PO4)2F 2.95 ;Na 3.05 V 1.8Fe 0.1 Ti 0.1 (PO4)2F 3.05 ;Na 2.9 V 1.8 Fe 0.1 Ti 0.1 (PO4)2F 2.9 ;Na 3.1 V 1.8 Fe 0.1 Ti 0.1 (PO4)2F 3.1 .

[0095] In some embodiments, the mass fraction of the carbon layer in the phosphate positive electrode material is 1.8% to 3%.

[0096] In some embodiments, the thickness of the carbon layer is 0.8 nm to 1.8 nm.

[0097] In this embodiment, controlling the mass fraction and / or thickness of the carbon layer within the above range is beneficial to ensuring that the carbon layer has a good coating effect on the inner core, and has the effects of improving electronic conductivity, enhancing structural stability, and inhibiting the occurrence of side reactions, thereby improving the electrochemical properties of the phosphate positive electrode material, such as specific capacity, rate performance, and cycle performance.

[0098] As an example, the mass fraction of the carbon layer in the phosphate positive electrode material includes but is not limited to 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%. Further, the mass fraction of the carbon layer in the phosphate positive electrode material is preferably 2.2% to 2.74%. Within this mass ratio range, the carbon layer has a better coating effect on the core, so that the electrochemical properties of the phosphate positive electrode material, such as specific capacity, rate performance and cycle performance, are further improved.

[0099] As an example, the thickness of the carbon layer includes but is not limited to 0.8nm, 0.9nm, 1nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm, 1.6nm, 1.7nm or 1.8nm. Further, the mass ratio of the core to the carbon layer is preferably 0.8nm to 1.5nm. The carbon layer within this thickness range is conducive to further improving the electronic conductivity, and the phosphate positive electrode material exhibits more excellent electrochemical performance.

[0100] In some embodiments, the D50 particle size of the phosphate positive electrode material is 6 μm to 10 μm, including but not limited to 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm.

[0101] In this embodiment, the phosphate positive electrode material has a suitable D50 particle size to ensure that Na + It can be embedded and released relatively quickly, improving the specific capacity and rate performance of the phosphate positive electrode material, and is easily dispersed in the electrode slurry, which is conducive to forming a positive electrode active coating with high flatness and good uniformity, thereby improving the flatness and stability of the positive electrode sheet with the phosphate positive electrode material.

[0102] In some embodiments, the powder resistivity of the phosphate positive electrode material is 100Ω·cm to 300Ω·cm, including but not limited to 100Ω·cm, 120Ω·cm, 140Ω·cm, 160Ω·cm, 180Ω·cm, 200Ω·cm, and 300Ω·cm, and is further preferably 100Ω·cm to 200Ω·cm.

[0103] In some embodiments, the average voltage platform of the phosphate positive electrode material is 3.6V to 3.7V, including but not limited to 3.6V, 3.61V, 3.62V, 3.63V, 3.64V, 3.65V, 3.67V, 3.68V, 3.69V or 3.7V, and is further preferably 3.65V to 3.7V.

[0104] In some embodiments, the first charge specific capacity of the phosphate positive electrode material at 0.1C is ≥120mAh / g, including but not limited to 120mAh / g, 121mAh / g, 122mAh / g, 123mAh / g, 124mAh / g, 125mAh / g, 126mAh / g, 127mAh / g, 128mAh / g, 129mAh / g or 130mAh / g, and is further preferably 122mAh / g to 127mAh / g.

[0105] In some embodiments, the first discharge specific capacity of the phosphate positive electrode material at 0.1C is ≥110mAh / g, including but not limited to 110mAh / g, 111mAh / g, 112mAh / g, 113mAh / g, 114mAh / g, 115mAh / g, 116mAh / g, 117mAh / g, 118mAh / g, 119mAh / g or 120mAh / g, and is further preferably 111mAh / g to 116mAh / g.

[0106] In some embodiments, the first coulombic efficiency of the phosphate positive electrode material at 0.1C is ≥90%, including but not limited to 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%, and is further preferably 90.1% to 93%.

[0107] In some embodiments, the first discharge specific capacity of the phosphate positive electrode material at 1C is ≥107mAh / g, including but not limited to 107mAh / g, 108mAh / g, 109mAh / g, 110mAh / g, 111mAh / g, 112mAh / g, 113mAh / g, 114mAh / g, 115mAh / g, 116mAh / g, 117mAh / g, 118mAh / g, 119mAh / g or 120mAh / g, and is further preferably 107mAh / g to 114mAh / g.

[0108] In some embodiments, the first discharge specific capacity of the phosphate positive electrode material at 5C is ≥102mAh / g, including but not limited to 102mAh / g, 103mAh / g, 104mAh / g, 105mAh / g, 106mAh / g, 107mAh / g, 108mAh / g, 109mAh / g, 110mAh / g, 111mAh / g, 112mAh / g, 113mAh / g, 114mAh / g or 115mAh / g, and is further preferably 102mAh / g to 110mAh / g.

[0109] In some embodiments, the 1C / 0.1C rate performance of the phosphate cathode material is ≥94%, including but not limited to 94%, 95%, 96%, 97%, 98%, 99% or 100%, and further preferably 94.46% to 98.5%.

[0110] In some embodiments, the room temperature cycle capacity retention rate of the phosphate positive electrode material at 1000 cycles and 1C rate is ≥ 70%, including but not limited to 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88% or 90%, and is further preferably 70% to 80%.

[0111] In this embodiment, the phosphate positive electrode material has high charge specific capacity, discharge specific capacity, first coulombic efficiency, rate performance and cycle performance, thereby ensuring that the positive electrode plate and the secondary battery have the advantages of high specific capacity, good rate performance and excellent cycle performance.

[0112] Please refer to Figure 1 In a second aspect, the present application provides a method for preparing a phosphate positive electrode material, comprising the following steps:

[0113] S1, a vanadium source, oxalic acid, a phosphorus source, a dopant and a solvent are mixed and reacted to obtain a mixed solution;

[0114] S2, the mixed liquid undergoes a first drying process and a first sintering process to obtain a precursor;

[0115] S3, the precursor, the sodium source, the fluorine source and the carbon source are mixed and ground to obtain a slurry;

[0116] S4, the slurry is subjected to a second drying treatment and a second sintering treatment to obtain a phosphate positive electrode material;

[0117] The dopant includes a first source and / or a second source, the first metal element in the first source and the second metal element in the second source each independently include one or more of Fe, Mn, Ti, Al and Mg, and the first metal element and the second metal element are different from each other.

[0118] In the technical solution of the embodiment of the present application, by performing a two-step sintering treatment, the first metal element and / or the second metal element in the dopant are more easily embedded in the crystal structure of the sodium vanadium fluorophosphate material, thereby improving the structural stability of the phosphate positive electrode material, and the first metal element and / or the second metal element are conducive to promoting the phosphate positive electrode material to melt more completely during the high-temperature sintering process, making the surface morphology more dense and smooth, thereby improving the compaction density, BET specific surface area, rate performance, and cycle performance of the phosphate positive electrode material. At the same time, the introduction of reducing oxalic acid in the preparation process of the precursor is conducive to the reduction of the vanadium element in the vanadium source, and the oxalic acid has almost no residual carbon after the sintering treatment, which is conducive to better controlling the carbon content and surface morphology of the phosphate positive electrode material, and improving the compaction density and BET specific surface area of ​​the phosphate positive electrode material. Therefore, the phosphate positive electrode material prepared in the embodiment of the present application not only has a significantly improved compaction density and BET specific surface area, but also a carbon layer is coated on the inner core of the phosphate positive electrode material, which further improves the electronic conductivity, structural stability and energy density of the phosphate positive electrode material, thereby ensuring its excellent performance in specific capacity, rate performance and cycle performance, which is conducive to the preparation of high energy density sodium ion batteries.

[0119] In some embodiments, the method for preparing the phosphate positive electrode material provided in the embodiments of the present application is used to prepare the phosphate positive electrode material as described above.

[0120] The following is a detailed description of the preparation method of the phosphate positive electrode material in a step-by-step manner.

[0121] S1, a vanadium source, oxalic acid, a phosphorus source, a dopant and a solvent are mixed and subjected to a reaction treatment to obtain a mixed solution.

[0122] In some embodiments, in step S1, the step of mixing the vanadium source, oxalic acid, phosphorus source, dopant and solvent, and reacting to obtain a mixed solution comprises:

[0123] The vanadium source and the solvent are mixed at a first temperature for a first time to obtain a first solution;

[0124] The first solution, the dopant and the oxalic acid are mixed at a second temperature for a second time to obtain a second solution;

[0125] The second solution and the phosphorus source are mixed at a third temperature for a third time to obtain a mixed solution;

[0126] Wherein, the first temperature is 80°C to 90°C, and the first time is 30min to 90min;

[0127] The second temperature is 90°C to 95°C, and the second time is 30min to 60min;

[0128] The third temperature is 90° C. to 100° C., and the third time is 12 min to 36 min.

[0129] In this embodiment, the first solution containing the vanadium source is used as the reaction base solution, and the dopant, oxalic acid and phosphorus source are gradually added to react. This is beneficial to ensure that the raw materials are mixed evenly and react fully, and makes it easier for the metal elements in the dopant to be embedded in the crystal structure of the precursor, which is beneficial to improve the purity and structural stability of the phosphate positive electrode material.

[0130] As an example, the first temperature includes but is not limited to 80℃, 81℃, 82℃, 83℃, 84℃, 85℃, 86℃, 87℃, 88℃, 89℃ or 90℃, and the first time is but is not limited to 30min, 40min, 50min, 60min, 70min, 80min or 90min; the second temperature is 90℃, 91℃, 92℃, 93℃, 94℃ or 95℃, and the second time is 30min, 35min, 40min, 45min, 50min, 55min or 60min; the third temperature is 90℃, 91℃, 92℃, 93℃, 94℃, 95℃, 96℃, 97℃, 98℃, 99℃ or 100℃, and the third time is 12min, 16min, 20min, 24min, 28min, 32min or 36min.

[0131] In some embodiments, when the dopant includes the first source and the second source, the amount ratio of the vanadium element in the vanadium source, the oxalic acid, the phosphorus element in the phosphorus source, the first metal element in the first source and the second metal element in the second source is (0.9-1.1): (2.5-3.5): 1: (0-0.5): (0-0.5), and the amount of the first metal element in the first source and the amount of the second metal element in the second source are not zero. It can be understood that in other embodiments, when the dopant includes the first source or the second source, the amount ratio of the vanadium element in the vanadium source, the oxalic acid, the phosphorus element in the phosphorus source, the first metal element in the first source (or the second metal element in the second source) is (0.9-1.1): (2.5-3.5): 1: (0-0.5), and the amount of the first metal element in the first source (and / or the second metal element in the second source) is not zero.

[0132] In this embodiment, by controlling the amount ratio of each element in the raw material, it is beneficial to fully react between the raw materials to obtain a high-purity precursor.

[0133] As an example, the molar ratio of the vanadium element in the vanadium source to the phosphorus element in the phosphorus source includes but is not limited to 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.98:1, 1:1, 1.02:1, 1.04:1, 1.06:1, 1.08:1 or 1.1:1; the molar ratio of oxalic acid to the phosphorus element in the phosphorus source includes but is not limited to 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1 or 3.5:1; the molar ratio of oxalic acid to the phosphorus element in the phosphorus source includes but is not limited to 3.5:1; The molar ratio of the phosphorus element in the phosphorus source and the second metal element in the second source includes but is not limited to 1:0, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45 or 1:0.5; the molar ratio of the phosphorus element in the phosphorus source and the second metal element in the second source includes but is not limited to 1:0, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45 or 1:0.5.

[0134] In some embodiments, the amount ratio of the phosphorus element in the phosphorus source, the first metal element in the first source, and the second metal element in the second source is 1:(0.05-0.3):(0.05-0.3).

[0135] In this embodiment, the feeding amounts of the first source and the second source are controlled within the above range, which is conducive to obtaining a phosphate positive electrode material with high compaction density, low powder resistivity and high average voltage platform voltage.

[0136] In some embodiments, the amount ratio of the phosphorus element in the phosphorus source, the first metal element in the first source, and the second metal element in the second source is 1:(0.05-0.25):(0.05-0.25).

[0137] In this embodiment, controlling the feeding amounts of the first source and the second source within the above range is beneficial to obtaining a phosphate positive electrode material with higher compaction density, lower powder resistivity, and higher average voltage platform voltage.

[0138] In some embodiments, the amount ratio of the phosphorus element in the phosphorus source, the first metal element in the first source, and the second metal element in the second source is 1:(0.1-0.2):(0.1-0.2).

[0139] In this embodiment, controlling the feeding amounts of the first source and the second source within the above range is more conducive to obtaining a phosphate positive electrode material with higher compaction density, lower powder resistivity, and higher average voltage platform voltage, thereby helping to further improve the electrochemical performance of the phosphate positive electrode material.

[0140] In some embodiments, the vanadium source includes one or more of vanadium pentoxide, vanadium trioxide, vanadium dioxide, ammonium metavanadate, sodium metavanadate, sodium orthovanadate, and vanadyl oxalate.

[0141] It can be understood that the vanadium source can be selected from any one of the above vanadium sources, or a combination of at least two thereof, for example: a combination of vanadium pentoxide and vanadium trioxide, a combination of vanadium pentoxide and vanadium dioxide, a combination of vanadium pentoxide and ammonium metavanadate, a combination of vanadium pentoxide and sodium metavanadate, a combination of vanadium pentoxide and sodium orthovanadate, a combination of vanadium pentoxide and vanadyl oxalate, a combination of vanadium pentoxide, vanadium trioxide, vanadium dioxide and ammonium metavanadate, etc. Further, the vanadium source is preferably vanadium pentoxide.

[0142] In some embodiments, the phosphorus source includes one or more of phosphoric acid, diammonium phosphate, monoammonium phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.

[0143] It can be understood that the phosphorus source can be selected from any one of the above phosphorus sources, or a combination of at least two thereof, for example: a combination of phosphoric acid and diammonium hydrogen phosphate, a combination of phosphoric acid and diammonium dihydrogen phosphate, a combination of phosphoric acid and ammonium phosphate, a combination of phosphoric acid and disodium hydrogen phosphate, a combination of phosphoric acid and sodium dihydrogen phosphate, a combination of diammonium hydrogen phosphate and diammonium dihydrogen phosphate, a combination of diammonium hydrogen phosphate and ammonium phosphate, a combination of diammonium hydrogen phosphate and disodium hydrogen phosphate, a combination of diammonium hydrogen phosphate and sodium dihydrogen phosphate, a combination of diammonium hydrogen phosphate, diammonium dihydrogen phosphate and ammonium phosphate, etc. Further, the phosphorus source is preferably diammonium dihydrogen phosphate.

[0144] In some embodiments, the first source includes one or more of oxides, hydroxides and salt compounds containing the first metal element, and the second source includes one or more of oxides, hydroxides and salt compounds containing the second metal element. Among them, the salt compound includes one or more of carbonates, sulfates, nitrates, hydrochlorides, acetates, oxalates and ethanolates. Further, the first source includes one or more of oxides and carbonates containing the first metal element, and the second source includes one or more of oxides and carbonates containing the second metal element. The use of oxides and / or carbonates as dopants is beneficial to avoid the introduction of anionic impurities, thereby ensuring that the phosphate positive electrode material has a higher purity.

[0145] In some embodiments, the first source and the second source each independently include one or more of ferric oxide, ferrosoferric oxide, manganese dioxide, manganese tetraoxide, manganese carbonate, titanium dioxide, aluminum oxide, magnesium oxide and magnesium carbonate, and the first metal element in the first source and the second metal element in the second source are different from each other.

[0146] As an example, combinations of the first source and the second source include, but are not limited to, a combination of ferric oxide and manganese dioxide, a combination of ferric oxide and manganese tetroxide, a combination of ferric oxide and manganese carbonate, a combination of ferric oxide and titanium dioxide, a combination of ferric oxide and aluminum oxide, a combination of ferric oxide and magnesium oxide, a combination of ferric oxide and magnesium carbonate, a combination of ferric oxide and manganese dioxide, a combination of ferric oxide and manganese tetroxide, a combination of ferric oxide and manganese carbonate, a combination of ferric oxide and titanium dioxide, a combination of ferric oxide and aluminum oxide, a combination of ferric oxide and magnesium oxide, a combination of ferric oxide and magnesium carbonate, a combination of manganese dioxide and titanium dioxide, a combination of manganese dioxide and aluminum oxide, a combination of manganese dioxide and magnesium oxide, a combination of manganese dioxide and magnesium carbonate, a combination of titanium dioxide and aluminum oxide, a combination of titanium dioxide and magnesium oxide, a combination of aluminum oxide and magnesium oxide, and the like.

[0147] In some embodiments, the solvent may be selected from one or more of distilled water, deionized water, pure water, and ultrapure water, and may further be deionized water.

[0148] S2. The mixed liquid undergoes a first drying treatment and a first sintering treatment to obtain a precursor.

[0149] In some embodiments, the step of subjecting the mixed liquid to a first drying treatment includes: subjecting the mixed liquid to a first spray drying treatment to obtain a first dried material.

[0150] In some embodiments, the sintering temperature of the first sintering process is 700° C. to 750° C., and the holding time is 1 h to 3 h.

[0151] In this embodiment, the first sintering treatment is carried out at 700° C. to 750° C. for 1 h to 3 h, which is beneficial to improving the crystallinity of the precursor, thereby improving the purity of the phosphate positive electrode material and further improving the electrochemical performance of the phosphate positive electrode material.

[0152] As an example, the sintering temperature of the first sintering treatment includes but is not limited to 700°C, 705°C, 710°C, 715°C, 720°C, 725°C, 730°C, 735°C, 740°C, 745°C or 750°C, and is more preferably 750°C; the holding time includes but is not limited to 1h, 1.5h, 2h, 2.5h or 3h, and is more preferably 1.5h.

[0153] In some embodiments, the first sintering process is performed under a protective atmosphere, and the protective gas in the protective atmosphere includes at least one of nitrogen, helium, neon, argon and xenon, and more preferably nitrogen or argon. High-temperature sintering in a protective atmosphere is beneficial to avoid the reaction of the precursor with moisture and oxygen during the heating, insulation and cooling stages, thereby improving the purity of the precursor.

[0154] In some embodiments, the precursor includes a vanadium phosphate material, which is expressed as V 1-x-y A x B y PO4. The meanings and value ranges of A, B, x, and y are as described above.

[0155] S3, the precursor, the sodium source, the fluorine source and the carbon source are mixed and ground to obtain a slurry.

[0156] In some embodiments, the molar ratio of phosphorus in the precursor, sodium in the sodium source, fluorine in the fluorine source, and carbon source is 1:(1.3-1.5):(1.3-1.5):(0.08-0.15).

[0157] In some embodiments, the molar ratio of phosphorus in the precursor, sodium in the sodium source, fluorine in the fluorine source, and carbon in the carbon source is 1:(1.3-1.5):(1.3-1.5):(0.48-0.9).

[0158] In this embodiment, by controlling the molar ratio of each element in the raw materials, it is beneficial to make the raw materials fully react to form a high-purity sodium vanadium fluorophosphate material, and to form a carbon layer with a relatively moderate thickness and carbon content on its surface.

[0159] As an example, the molar ratio of the phosphorus element in the precursor to the sodium element in the sodium source includes but is not limited to 1:1.3, 1:1.32, 1:1.34, 1:1.36, 1:1.38, 1:1.4, 1:1.42, 1:1.44, 1:1.46, 1:1.48, 1:1.5; the molar ratio of the phosphorus element in the precursor to the fluorine element in the fluorine source includes but is not limited to 1:1.3, 1:1 .32, 1:1.34, 1:1.36, 1:1.38, 1:1.4, 1:1.42, 1:1.44, 1:1.46, 1:1.48, 1:1.5; the molar ratio of the phosphorus element in the precursor to the carbon element in the carbon source includes but is not limited to 1:0.48, 1:0.54, 1:0.6, 1:0.66, 1:0.72, 1:0.78, 1:0.84 or 1:0.9.

[0160] In some embodiments, the sodium source includes one or more of sodium fluoride, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and sodium phosphate.

[0161] It is understandable that the sodium source can be selected from any one of the above sodium sources, or a combination of at least two thereof, for example: a combination of sodium fluoride and sodium hydroxide, a combination of sodium fluoride and sodium carbonate, a combination of sodium fluoride and sodium bicarbonate, a combination of sodium fluoride and sodium nitrate, a combination of sodium fluoride and sodium acetate, a combination of sodium fluoride and sodium oxalate, a combination of sodium fluoride and sodium acetate, a combination of sodium fluoride and sodium dihydrogen phosphate, a combination of sodium fluoride and disodium hydrogen phosphate, a combination of sodium fluoride and sodium phosphate, a combination of sodium fluoride, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium phosphate, etc. Further, the sodium source is preferably sodium fluoride.

[0162] In some embodiments, the fluoride source includes one or more of sodium fluoride, ammonium fluoride, and hydrogen fluoride.

[0163] It is understandable that the fluorine source can be selected from any one of the above fluorine sources, or a combination of at least two thereof, such as a combination of sodium fluoride and ammonium fluoride, a combination of sodium fluoride and hydrogen fluoride, and a combination of sodium fluoride, ammonium fluoride and hydrogen fluoride. Further, the fluorine source is preferably sodium fluoride.

[0164] In some embodiments, the carbon source comprises one or more of glucose, polyethylene glycol, sucrose, and ascorbic acid.

[0165] In this embodiment, the selection of different carbon sources is beneficial to adjusting the compaction density, BET specific surface area and electrochemical performance of the phosphate positive electrode material, thereby improving the comprehensive performance of the phosphate positive electrode material.

[0166] It is understandable that the carbon source can be selected from any one of the above carbon sources, or a combination of at least two thereof, for example: a combination of glucose and polyethylene glycol, a combination of glucose and sucrose, a combination of glucose and ascorbic acid, a combination of polyethylene glycol and sucrose, a combination of polyethylene glycol and ascorbic acid, a combination of sucrose and ascorbic acid, and a combination of glucose, polyethylene glycol, sucrose and ascorbic acid, etc. Further, the carbon source is preferably glucose, which can form a carbon layer with fine particles and a dense surface, which is beneficial to improve the compaction density of the phosphate positive electrode material.

[0167] In some embodiments, the grinding process includes one or more of a ball milling process and a sand milling process.

[0168] In this embodiment, ball milling and / or sand milling are used to make different materials evenly mixed and fully contacted, and the D50 particle size of the solid particles in the slurry is reduced, which is beneficial to improving the subsequent reaction rate and product uniformity.

[0169] In some embodiments, the precursor, sodium source, fluorine source and carbon source are mixed and ground to obtain a slurry, the step comprising: after the precursor, sodium source, fluorine source and carbon source are mixed, water is added for ball milling to obtain a slurry with a solid content of 15% to 20% and a D50 particle size of 3μm to 5μm.

[0170] It can be understood that the solid content of the slurry is the mass fraction of the solid in the slurry. As an example, the solid content of the slurry includes but is not limited to 15%, 16%, 17%, 18%, 19%, 20%; the D50 particle size of the solid particles in the slurry includes but is not limited to 3μm, 3.5μm, 4μm, 4.5μm or 5μm.

[0171] S4, the slurry is subjected to a second drying treatment and a second sintering treatment to obtain a phosphate positive electrode material;

[0172] In some embodiments, the step of subjecting the slurry to a second drying treatment includes: subjecting the slurry to a second spray drying treatment, with an air inlet temperature of 240°C to 260°C and an air outlet temperature of 90°C to 100°C, to obtain a second dried material.

[0173] In this embodiment, the inlet air temperature and outlet air temperature of the second spray drying are controlled, which is beneficial to fully remove the moisture in the second dried material and avoid excessively high outlet air temperature causing partial decomposition of the carbon source and reducing the carbon content of the final phosphate positive electrode material.

[0174] As an example, the inlet air temperature of the second spray drying treatment includes but is not limited to 240°C, 242°C, 244°C, 246°C, 248°C, 250°C, 252°C, 254°C, 256°C, 258°C or 260°C; the outlet air temperature of spray drying includes but is not limited to 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C.

[0175] In some embodiments, the sintering temperature of the second sintering process is 550° C. to 750° C., and the holding time is 8 h to 12 h.

[0176] In this embodiment, the second sintering treatment is carried out at 550°C to 750°C for 8h to 12h, which effectively controls energy consumption while avoiding the formation of excessive impurities during the sintering process, helping to improve the crystallinity and purity of the phosphate positive electrode material, thereby improving the electrochemical properties such as charge specific capacity and discharge specific capacity.

[0177] As an example, the sintering temperature of the second sintering treatment includes but is not limited to 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃ or 750℃; the holding time includes but is not limited to 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h or 12h.

[0178] In some embodiments, the second sintering treatment is performed under a protective atmosphere, and the protective gas in the protective atmosphere includes at least one of nitrogen, helium, neon, argon and xenon, and more preferably nitrogen or argon. High-temperature sintering in a protective atmosphere is beneficial to avoid the reaction of the phosphate positive electrode material with moisture and oxygen during the heating, insulation and cooling stages, thereby improving the purity of the phosphate positive electrode material and reducing the adverse effects on the subsequent preparation process and electrical properties of the positive electrode sheet and the secondary battery.

[0179] In some embodiments, after the second sintering treatment, the following steps are also included: crushing and screening the sintered material obtained after the second sintering treatment to obtain a phosphate positive electrode material with a D50 particle size of 6μm to 8μm and a D100 particle size of ≤30μm.

[0180] In this embodiment, by controlling the D50 particle size of the phosphate positive electrode material, it is beneficial to + It can quickly transport the positive electrode and improve its uniformity of dispersion in the electrode slurry, which is conducive to forming a positive electrode active coating with high flatness and good uniformity, thereby improving the consistency and stability of the positive electrode sheet.

[0181] As an example, the D50 particle size of the phosphate positive electrode material includes but is not limited to 6μm, 6.5μm, 7μm, 7.5μm or 8μm; the D100 particle size of the phosphate positive electrode material includes but is not limited to 30μm, 28μm, 25μm, 22μm, 20μm, 18μm, 15μm, 12μm or 10μm.

[0182] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the phosphate positive electrode material provided in the first aspect of the present application, or comprising a phosphate positive electrode material prepared by the preparation method of the phosphate positive electrode material provided in the second aspect of the present application.

[0183] In this embodiment, the positive electrode plate includes the above-mentioned phosphate positive electrode material, and thus has the advantages of high charge specific capacity and discharge specific capacity, good rate performance and excellent cycle performance.

[0184] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode plate provided in the third aspect of the present application.

[0185] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of high charge specific capacity and discharge specific capacity, good rate performance and excellent cycle performance.

[0186] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0187] 1. Preparation method

[0188] Example 1

[0189] The preparation method of the phosphate positive electrode material provided in this embodiment is as follows:

[0190] (1) Vanadium pentoxide (V2O5) and deionized water are mixed, heated and stirred at 90°C for 0.5 h to completely dissolve the vanadium pentoxide (V2O5), thereby obtaining an orange-red first solution; a dopant is added to the first solution, oxalic acid (H2C2O4) is slowly added, and after the solution changes color, the solution is heated and stirred at 90°C for 1 h to obtain a dark green second solution; ammonium dihydrogen phosphate (NH4H2PO4) is slowly added to the second solution, and after the solution turns into a clear blue color, the solution is heated and stirred at 90°C for 0.5 h to obtain a blue clear mixed solution.

[0191] Among them, the dopant includes a first source and a second source, the first source is ferric oxide (Fe2O3), the second source is titanium dioxide (TiO2), the material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in diammonium phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 1:3:1:0.1:0.1.

[0192] (2) spray drying the mixed liquid to obtain a light green first dried material; placing the first dried material in a nitrogen atmosphere sintering furnace, performing a first sintering treatment at 750° C., and keeping the temperature for 1.5 hours to obtain a dark green precursor.

[0193] (3) The precursor, sodium fluoride, carbon source and deionized water are ball-milled to mix the materials evenly to obtain a slurry with a solid content of 18% and a D50 particle size of 4 μm; the slurry is spray-dried, and the air inlet temperature is controlled at 255°C and the air outlet temperature is controlled at 90°C to obtain a gray-green second dried material; the second dried material is placed in a nitrogen atmosphere sintering furnace, and a second sintering treatment is performed at 700°C, and the temperature is kept for 10 hours to obtain a sintered material; the sintered material is crushed and sieved to obtain a phosphate positive electrode material with a D50 particle size of 6 μm and a D100 particle size ≤30 μm.

[0194] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.4:1.4:0.6, and the carbon source is glucose.

[0195] Example 2

[0196] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0197] (1) Vanadium pentoxide (V2O5) and deionized water are mixed, heated and stirred at 80°C for 0.5 h to completely dissolve the vanadium pentoxide (V2O5), thereby obtaining an orange-red first solution; a dopant is added to the first solution, and oxalic acid (H2C2O4) is slowly added. After the solution changes color, the solution is heated and stirred at 90°C for 0.5 h to obtain a dark green second solution; ammonium dihydrogen phosphate (NH4H2PO4) is slowly added to the second solution, and after the solution turns into a clear blue color, the solution is heated and stirred at 90°C for 12 min to obtain a blue clear mixed solution.

[0198] Among them, the dopant includes a first source and a second source, the first source is ferric oxide (Fe2O3), the second source is titanium dioxide (TiO2), the material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in diammonium phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 1:3:1:0.2:0.1.

[0199] (2) spray drying the mixed liquid to obtain a light green first dried material; placing the first dried material in a nitrogen atmosphere sintering furnace, performing a first sintering treatment at 700° C., and keeping the temperature for 1 hour to obtain a dark green precursor.

[0200] (3) The precursor, sodium fluoride, carbon source and deionized water are ball-milled to mix the materials evenly to obtain a slurry with a solid content of 15% and a D50 particle size of 3 μm; the slurry is spray-dried, and the air inlet temperature is controlled at 250°C and the air outlet temperature is controlled at 90°C to obtain a gray-green second dried material; the second dried material is placed in a nitrogen atmosphere sintering furnace, and a second sintering treatment is performed at 550°C, and the temperature is kept for 8 hours to obtain a sintered material; the sintered material is crushed and sieved to obtain a phosphate positive electrode material with a D50 particle size of 6 μm and a D100 particle size ≤30 μm.

[0201] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.4:1.4:0.6, and the carbon source is glucose.

[0202] Example 3

[0203] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0204] (1) Vanadium pentoxide (V2O5) and deionized water are mixed, heated and stirred at 90°C for 1.5 hours to completely dissolve the vanadium pentoxide (V2O5), thereby obtaining an orange-red first solution; a dopant is added to the first solution, and oxalic acid (H2C2O4) is slowly added, and after the solution changes color, it is heated and stirred at 95°C for 1 hour to obtain a dark green second solution; ammonium dihydrogen phosphate (NH4H2PO4) is slowly added to the second solution, and after the solution turns into a clear blue, it is heated and stirred at 100°C for 36 minutes to obtain a blue clear mixed solution.

[0205] Among them, the dopant includes a first source and a second source, the first source is ferric oxide (Fe2O3), the second source is titanium dioxide (TiO2), the material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in diammonium phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 1:3:1:0.2:0.2.

[0206] (2) spray drying the mixed liquid to obtain a light green first dried material; placing the first dried material in a nitrogen atmosphere sintering furnace, performing a first sintering treatment at 750° C., and keeping the temperature for 3 hours to obtain a dark green precursor.

[0207] (3) The precursor, sodium fluoride, carbon source and deionized water are ball-milled to mix the materials evenly to obtain a slurry with a solid content of 20% and a D50 particle size of 5 μm; the slurry is spray-dried, and the air inlet temperature is controlled at 260°C and the air outlet temperature is controlled at 90°C to obtain a gray-green second dried material; the second dried material is placed in a nitrogen atmosphere sintering furnace, and a second sintering treatment is performed at 750°C, and the temperature is kept for 12 hours to obtain a sintered material; the sintered material is crushed and sieved to obtain a phosphate positive electrode material with a D50 particle size of 6 μm and a D100 particle size ≤30 μm.

[0208] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.4:1.4:0.6, and the carbon source is glucose.

[0209] Example 4

[0210] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0211] The material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in ammonium dihydrogen phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 1:3:1:0.05:0.05.

[0212] Example 5

[0213] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0214] The material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in ammonium dihydrogen phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 1:3:1:0.3:0.3.

[0215] Example 6

[0216] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0217] The first source is ferroferric oxide (Fe3O4), the second source is manganese tetraoxide (Mn3O4), and the molar ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in diammonium phosphate (NH4H2PO4), iron element in the first source and manganese element in the second source is 1:3:1:0.1:0.1.

[0218] Example 7

[0219] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0220] The first source is manganese carbonate (MnCO3), the second source is aluminum oxide (Al2O3), the molar ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in diammonium phosphate (NH4H2PO4), manganese element in the first source and aluminum element in the second source is 1:3:1:0.1:0.1.

[0221] Example 8

[0222] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0223] The first source is titanium dioxide (TiO2), the second source is magnesium oxide (MgO), and the molar ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in diammonium phosphate (NH4H2PO4), titanium element in the first source and magnesium element in the second source is 1:3:1:0.1:0.1.

[0224] Example 9

[0225] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0226] The first source is ferric oxide (Fe2O3), and no second source is added. The molar ratio of vanadium in vanadium pentoxide (V2O5), oxalic acid, phosphorus in diammonium phosphate (NH4H2PO4) and iron in the first source is 1:3:1:0.1.

[0227] Example 10

[0228] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0229] The first source is not added, the second source is titanium dioxide (TiO2), the molar ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in diammonium phosphate (NH4H2PO4) and titanium element in the second source is 1:3:1:0.1.

[0230] Embodiment 11

[0231] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0232] The first source is ferric oxide (Fe2O3) and aluminum oxide (Al2O3), the second source is titanium dioxide (TiO2) and manganese dioxide (MnO2), and the molar ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in diammonium phosphate (NH4H2PO4), iron element in the first source, aluminum element in the first source, titanium element in the second source and manganese element in the second source is 1:3:1:0.1:0.1:0.1:0.1.

[0233] Example 12

[0234] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0235] The material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in ammonium dihydrogen phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 1:2.5:1:0.1:0.1.

[0236] Example 13

[0237] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0238] The material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in ammonium dihydrogen phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 1:3.5:1:0.1:0.1.

[0239] Embodiment 14

[0240] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0241] In step (2), the sintering temperature of the first sintering treatment is 700° C. and the holding time is 3 hours.

[0242] Embodiment 15

[0243] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0244] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.4:1.4:0.48, and the carbon source is glucose.

[0245] Example 16

[0246] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0247] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.4:1.4:0.9, and the carbon source is glucose.

[0248] Embodiment 17

[0249] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0250] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and the carbon source is 1:1.4:1.4:0.1, and the carbon source is PEG-2000.

[0251] Embodiment 18

[0252] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0253] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.4:1.4:0.6, and the carbon source is ascorbic acid.

[0254] Embodiment 19

[0255] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in Embodiment 1, except that the types of vanadium source, phosphorus source, sodium source and fluorine source are different, as follows:

[0256] (1) Ammonium metavanadate (NH4VO3) and deionized water are mixed, heated and stirred at 80°C for 0.5 h to completely dissolve the ammonium metavanadate (NH4VO3), thereby obtaining an orange-red first solution; a dopant is added to the first solution, and oxalic acid (H2C2O4) is slowly added. After the solution changes color, the solution is heated and stirred at 90°C for 1 h to obtain a dark green second solution; diammonium hydrogen phosphate ((NH4)2HPO4) is slowly added to the second solution, and after the solution turns into a clear blue color, the solution is heated and stirred at 90°C for 0.5 h to obtain a clear blue mixed solution.

[0257] The dopant includes a first source and a second source, the first source is ferric oxide (Fe2O3), the second source is titanium dioxide (TiO2), and the molar ratio of vanadium element in ammonium metavanadate (NH4VO3), oxalic acid, phosphorus element in diammonium hydrogen phosphate ((NH4)2HPO4), iron element in the first source and titanium element in the second source is 1:3:1:0.1:0.1.

[0258] (2) spray drying the mixed liquid to obtain a light green first dried material; placing the first dried material in a nitrogen atmosphere sintering furnace, performing a first sintering treatment at 750° C., and keeping the temperature for 1.5 hours to obtain a dark green precursor.

[0259] (3) The precursor, sodium hydroxide, ammonium fluoride, carbon source and deionized water are ball-milled to mix the materials evenly to obtain a slurry with a solid content of 15% and a D50 particle size of 4 μm; the slurry is spray-dried, and the inlet air temperature is controlled at 250°C and the outlet air temperature is controlled at 90°C to obtain a gray-green second dried material; the second dried material is placed in a nitrogen atmosphere sintering furnace, and a second sintering treatment is performed at 700°C, and the temperature is kept for 10 hours to obtain a sintered material; the sintered material is crushed and sieved to obtain a phosphate positive electrode material with a D50 particle size of 6 μm and a D100 particle size ≤30 μm.

[0260] Among them, the molar ratio of phosphorus in the precursor, sodium in sodium hydroxide, fluorine in ammonium fluoride, and carbon in the carbon source is 1:1.4:1.4:0.1, and the carbon source is glucose.

[0261] Embodiment 20

[0262] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0263] The material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in ammonium dihydrogen phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 0.9:3:1:0.1:0.1.

[0264] Embodiment 21

[0265] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0266] The material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in ammonium dihydrogen phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 1:3:1:0.1:0.25.

[0267] Embodiment 22

[0268] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0269] The material ratio of vanadium element in vanadium pentoxide (V2O5), oxalic acid, phosphorus element in ammonium dihydrogen phosphate (NH4H2PO4), iron element in the first source and titanium element in the second source is 1:3:1:0.25:0.1.

[0270] Embodiment 23

[0271] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0272] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.3:1.3:0.6, and the carbon source is glucose.

[0273] Embodiment 24

[0274] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0275] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.5:1.5:0.6, and the carbon source is glucose.

[0276] Embodiment 25

[0277] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0278] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.2:1.2:0.6, and the carbon source is glucose.

[0279] Embodiment 26

[0280] The preparation method of the phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:

[0281] The molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.6:1.6:0.6, and the carbon source is glucose.

[0282] Comparative Example 1

[0283] The preparation method of the phosphate positive electrode material provided in this comparative example is the same or similar to that in Example 1, except that:

[0284] No dopant is added in step (1), and the preparation method is specifically as follows:

[0285] (1) Vanadium pentoxide (V2O5) and deionized water are mixed, heated and stirred at 90°C for 0.5 h to completely dissolve the vanadium pentoxide (V2O5), thereby obtaining an orange-red first solution; oxalic acid (H2C2O4) is slowly added to the first solution, and after the solution changes color, it is heated and stirred at 90°C for 1 h to obtain a dark green second solution; ammonium dihydrogen phosphate (NH4H2PO4) is slowly added to the second solution, and after the solution turns into a clear blue, it is heated and stirred at 90°C for 0.5 h to obtain a blue clear mixed solution.

[0286] The molar ratio of vanadium in vanadium pentoxide (V2O5), oxalic acid and phosphorus in ammonium dihydrogen phosphate (NH4H2PO4) is 1:3:1.

[0287] (2) Same as step (2) of Example 1.

[0288] (3) Same as step (3) of Example 1.

[0289] Comparative Example 2

[0290] The preparation method of the phosphate positive electrode material provided in this comparative example is the same or similar to that in Example 1, except that:

[0291] No oxalic acid is added in step (1), and the preparation method is specifically as follows:

[0292] (1) Vanadium pentoxide (V2O5) and deionized water are mixed, heated and stirred at 90°C for 0.5 h to completely dissolve the vanadium pentoxide (V2O5), thereby obtaining an orange-red first solution; a dopant is added to the first solution, and heated and stirred at 90°C for 1 h to obtain a red second solution; ammonium dihydrogen phosphate (NH4H2PO4) is slowly added to the second solution, and after the solution turns light blue, heating and stirring are continued at 90°C for 0.5 h to obtain a blue clear mixed solution.

[0293] Among them, the dopant includes a first source and a second source, the first source is ferric oxide (Fe2O3), the second source is titanium dioxide (TiO2), and the material ratio of the vanadium element in vanadium pentoxide (V2O5), the phosphorus element in diammonium phosphate (NH4H2PO4), the iron element in the first source and the titanium element in the second source is 1:1:0.1:0.1.

[0294] (2) Same as step (2) of Example 1.

[0295] (3) Same as step (3) of Example 1.

[0296] Comparative Example 3

[0297] The preparation method of the phosphate positive electrode material provided in this comparative example is the same or similar to that in Example 1, except that:

[0298] In step (1), oxalic acid is replaced with an equal amount of citric acid.

[0299] Comparative Example 4

[0300] The preparation method of the phosphate positive electrode material provided in this comparative example is the same or similar to that in Example 1, except that:

[0301] In step (2), the first dried material is not subjected to the first sintering treatment. The preparation method is specifically as follows:

[0302] (1) Prepare a mixed solution according to step (1) of Example 1.

[0303] (2) The mixed solution is spray-dried to obtain a light green first dried material.

[0304] (3) The first dried material, sodium fluoride, carbon source and deionized water are ball-milled to mix the materials evenly to obtain a slurry with a solid content of 15% and a D50 particle size of 4 μm; the slurry is spray-dried, and the inlet air temperature is controlled at 250°C and the outlet air temperature is controlled at 90°C to obtain a gray-green second dried material; the second dried material is placed in a nitrogen atmosphere sintering furnace, and a second sintering treatment is performed at 700°C, and the temperature is kept for 10 hours to obtain a sintered material; the sintered material is crushed and sieved to obtain a phosphate positive electrode material with a D50 particle size of 6 μm and a D100 particle size ≤30 μm.

[0305] Among them, the molar ratio of phosphorus in the first dried material, sodium and fluorine in sodium fluoride, and carbon in the carbon source is 1:1.4:1.4:0.1, and the carbon source is glucose.

[0306] Comparative Example 5

[0307] The preparation method of the phosphate positive electrode material provided in this comparative example is the same or similar to that in Example 1, except that:

[0308] No dopant is added in step (1), and a dopant is added in step (3). The preparation method is specifically as follows:

[0309] (1) Vanadium pentoxide (V2O5) and deionized water are mixed, heated and stirred at 90°C for 0.5 h to completely dissolve the vanadium pentoxide (V2O5), and an orange-red first solution is obtained; oxalic acid (H2C2O4) is slowly added to the first solution, and after the solution changes color, it is heated and stirred at 90°C for 0.5 h to obtain a dark green second solution; ammonium dihydrogen phosphate (NH4H2PO4) is slowly added to the second solution, and after the solution turns into a clear blue, it is heated and stirred at 90°C for 0.5 h to obtain a blue clear mixed solution.

[0310] The molar ratio of vanadium in vanadium pentoxide (V2O5), oxalic acid and phosphorus in ammonium dihydrogen phosphate (NH4H2PO4) is 1:3:1.

[0311] (2) spray drying the mixed liquid to obtain a light green first dried material; placing the first dried material in a nitrogen atmosphere sintering furnace, performing a first sintering treatment at 750° C., and keeping the temperature for 1.5 hours to obtain a dark green precursor.

[0312] (3) The precursor, sodium fluoride, carbon source, dopant and deionized water are ball-milled to mix the materials evenly to obtain a slurry with a solid content of 15% and a D50 particle size of 4 μm; the slurry is spray-dried, and the inlet air temperature is controlled at 250°C and the outlet air temperature is controlled at 90°C to obtain a gray-green second dried material; the second dried material is placed in a nitrogen atmosphere sintering furnace, and a second sintering treatment is performed at 700°C, and the temperature is kept for 10 hours to obtain a sintered material; the sintered material is crushed and sieved to obtain a phosphate positive electrode material with a D50 particle size of 6 μm and a D100 particle size of <30 μm.

[0313] Among them, the carbon source is glucose; the dopant includes a first source and a second source, the first source is ferric oxide (Fe2O3), and the second source is titanium dioxide (TiO2); the molar ratio of phosphorus in the precursor, sodium and fluorine in sodium fluoride, carbon in the carbon source, iron in the first source and titanium in the second source is 1:1.4:1.4:0.6:0.1:0.1.

[0314] 2. Test Method

[0315] 1. Property test of phosphate cathode materials

[0316] (1) Scanning electron microscopy (SEM) test: The morphology was characterized using a field emission scanning electron microscope (MERLIN Compact and Quanta 200FEG) produced by Zeiss.

[0317] (2) Transmission electron microscopy (TEM) test: A transmission electron microscope (TEM) of the model FEI Tecnai G2 F20 X-Twin produced by Thermo Fisher Scientific Inc. was used to perform morphological analysis and measure the thickness of the carbon layer.

[0318] (3) Element content: The content of each element was tested using an inductively coupled plasma optical emission spectrometer (ICP-OES), and the carbon content was tested using an infrared carbon-sulfur analyzer.

[0319] (4) Compaction density: The compaction density was tested using the UTM7305 battery powder compaction density meter provided by Shenzhen Sansi Zongheng Technology Co., Ltd. The test pressure was 3T and the pressing time was 30S.

[0320] (5) Specific surface area: The specific surface area was measured using a BELSORP MaxII specific surface area analyzer produced by Japan-Michiko BELCO.

[0321] (6) Powder resistivity: tested by four-probe method with a test pressure of 10 MPa.

[0322] 2. Properties test of secondary batteries

[0323] The phosphate positive electrode material was mixed with conductive carbon black and PVDF binder in a mass ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was coated on an aluminum foil with a thickness of 12 μm to form a positive electrode slurry layer with a thickness of 80 μm; then it was placed in an oven at 110°C and dried for 10 hours, and after drying, it was punched into a circular electrode piece with a diameter of 15 mm and pressed to a compact density of 1.8 g / cm 3 Roll-pressing is performed to obtain a positive electrode sheet.

[0324] Sodium hexafluorophosphate (NaPF6) is used as sodium salt, and ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) with a volume ratio of 1:1:1 are used as organic solvents. The sodium salt is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M; a pure sodium sheet with a purity of 99% is used as the counter electrode, and the battery is assembled with the positive electrode sheet and the electrolyte in the LG2400 / 1000TS glove box produced by Weige Gas Purification Technology (Suzhou) Co., Ltd. to obtain a button half-cell.

[0325] The CT3002A battery performance test system produced by Wuhan Blue Electric Electronic Technology Co., Ltd. was used to conduct rate performance tests on button half-cells. The test temperature was 25°C, the voltage range was 2V to 4.35V, and the rate range was 0.1C to 3C.

[0326] III. Analysis of test results of various embodiments and comparative examples

[0327] The above test results can be found in Figure 2 to Figure 5 And Table 1 ~ Table 2.

[0328] Table 1

[0329]

[0330] Table 2

[0331]

[0332] It can be seen from Table 1 that in the phosphate positive electrode materials of Examples 1 to 26, the mass fraction of each element is controlled within the following range: Na element 15.47% to 17.54%, V element 17.95% to 24.11%, A element ≤ 2.99%, B element ≤ 3%, P element 14.14% to 14.82%, F element 13.34% to 17.26%, C element 2.2% to 2.74%, and according to TEM test, the thickness of the carbon layer is 0.8nm to 1.5nm. This proves that the phosphate positive electrode material includes a core and a carbon layer covering the core, and the core satisfies the following expression: Na3V 2-x-y A x B y (PO4)2F3, where 0≤x≤0.5, 0≤y≤0.5, and x and y are not zero at the same time.

[0333] It can be seen from Table 2 that the compacted density of the phosphate positive electrode materials of Examples 1 to 26 is 2 g / cm 3 ~2.1g / cm 3 , BET specific surface area is 10m 2 / g~15.3m 2 / g, powder resistivity is 100Ω·cm~300Ω·cm, average voltage platform is 3.61V~3.7V, 0.1C first charge specific capacity is 115mAh / g~127mAh / g, 0.1C first discharge specific capacity is 105mAh / g~116mAh / g, 0.1C first coulombic efficiency is 90%~93.04%, 1C first discharge specific capacity is 100mAh / g~114mAh / g, 5C first discharge specific capacity is 92mAh / g~110mAh / g, 1C / 0.1C rate performance is 91.4%~98.5%, and the normal temperature cycle capacity retention rate at 1C rate for 1000 cycles is 66%~80%.

[0334] Depend on Figure 2 and Figure 3 By comparison, it can be seen that the surface of the phosphate cathode material of Example 1 is dense and smooth, without crystal particles, so it has a higher compaction density and BET specific surface area; the carbon layer surface of the phosphate cathode material of Comparative Example 1 presents porous wrinkles, and obvious crystal particles can be observed, which has an adverse effect on the compaction density and BET specific surface area. Figure 4 and Figure 5 It can be seen from the comparison that compared with Comparative Example 1, the phosphate positive electrode material of Example 1 has a higher and more stable discharge platform in the charge and discharge curve diagram. As shown in Table 2, compared with Comparative Example 1, the phosphate positive electrode material of Example 1 is doped with Fe and Ti elements, which significantly improves its compaction density, BET specific surface area and electrochemical performance, indicating that the co-doping treatment of Fe and Ti elements not only optimizes the electronic conductivity of the phosphate positive electrode material and effectively improves the average voltage platform, but also makes the phosphate positive electrode material have a higher compaction density and a larger BET specific surface area, thereby ensuring that the phosphate positive electrode material has excellent performance in capacity, rate performance and cycle performance.

[0335] Compared with Example 1, in Comparative Example 5, no dopant is added in step (1), but a dopant is added in step (3). During the sintering process of the precursor and the dopant, the metal cations in the dopant are difficult to be completely embedded in the crystal structure, which not only significantly reduces the compaction density and BET specific surface area, but also leads to structural instability of the phosphate positive electrode material, a significant decrease in electronic conductivity, a decrease in the average voltage platform, and a significant decrease in the discharge specific capacity, first coulomb efficiency, rate performance and cycle performance of the phosphate positive electrode material. This shows that doping the precursor with a dopant is conducive to more fully embedding the metal cations in the crystal structure of the phosphate positive electrode material, thereby improving the compaction density and BET specific surface area of ​​the phosphate positive electrode material, and improving its structural stability, electronic conductivity and average voltage platform, so that it exhibits more excellent electrochemical performance.

[0336] The difference between the phosphate positive electrode materials of Examples 1 to 5 and Examples 21 to 22 lies in the doping amounts of Fe and Ti elements. Combining the corresponding results in Tables 1 and 2, it can be seen that when 0.05≤x≤0.2 and 0.05≤y≤0.2, it is more conducive to obtaining a phosphate positive electrode material with lower powder resistivity and higher average voltage platform voltage.

[0337] The difference between the phosphate positive electrode materials of Examples 1 and 6 to 8 is that the types of element A and element B are different. Compared with Example 1, the compaction density of the phosphate positive electrode materials of Examples 6 to 8 is reduced, the powder resistivity is improved to a certain extent, the average voltage platform is reduced, and the capacity, first coulomb efficiency, rate performance and cycle performance are reduced to varying degrees, indicating that compared with the combination of Fe+Mn, Mn+Al, Ti+Mg, etc., the phosphate positive electrode material has better compaction density, BET specific surface area and electrochemical performance by co-doping with the combination of Fe element and Ti element.

[0338] The difference between Example 1, Example 12 and Example 13 is that the amount of oxalic acid in step (1) is different. Compared with Example 1, the amount of oxalic acid in Example 12 is reduced, so that the carbon content and the thickness of the carbon layer are reduced, and the amount of oxalic acid in Example 13 is increased, so that the carbon content and the thickness of the carbon layer are increased, and the compacted density, BET specific surface area and electrochemical performance of the phosphate positive electrode material of Examples 12 to 13 are reduced. It can be seen that in the process of preparing the phosphate positive electrode material, adding an appropriate amount of oxalic acid helps to accurately control the carbon content and the thickness of the carbon layer of the phosphate positive electrode material, thereby improving the compacted density, BET specific surface area and electrochemical performance of the phosphate positive electrode material. Compared with Example 1, Comparative Example 2 did not add oxalic acid, and Comparative Example 3 replaced oxalic acid with an equal amount of citric acid. The compacted density, BET specific surface area and electrochemical performance of the phosphate positive electrode material were significantly deteriorated, indicating that oxalic acid not only plays a reducing role, but also plays a role in controlling the carbon content and surface morphology of the phosphate positive electrode material, thereby improving the comprehensive performance of the phosphate positive electrode material.

[0339] Compared with Example 1, Comparative Example 4 did not perform the first sintering treatment, and the crystallinity of the obtained precursor was reduced, which reduced the purity of the subsequently obtained phosphate positive electrode material, thereby significantly reducing the carbon content, carbon layer thickness, compacted density, BET specific surface area and electrochemical performance of the phosphate positive electrode material obtained in Comparative Example 4.

[0340] The difference between the phosphate positive electrode materials of Example 1 and Examples 15-16 is that the amount of carbon source in step (3) is different. Combining the corresponding results of Table 1 and Table 2, it can be seen that when the molar ratio of the phosphorus element in the precursor to the carbon element in the carbon source (glucose) is 1:0.6, it is more conducive to obtaining a phosphate positive electrode material with higher compaction density, lower powder resistivity, and higher average voltage platform voltage. The difference between the phosphate positive electrode materials of Example 1 and Examples 17-18 is that the type of carbon source in step (3) is different. Combining the corresponding results of Table 1 and Table 2, it can be seen that compared with PEG-2000 and ascorbic acid, when glucose is used as the carbon source, it is more conducive to obtaining a phosphate positive electrode material with higher compaction density, lower powder resistivity, and higher average voltage platform voltage.

[0341] Compared with Examples 25 to 26, Examples 1 and Examples 23 to 24 have higher compaction densities, indicating that controlling the phosphorus element in the precursor, the sodium element in the sodium source, and the fluorine element in the fluorine source within the range of 1:(1.3 to 1.5):(1.3 to 1.5) is more conducive to improving the compaction density of the phosphate positive electrode material and obtaining better electrochemical performance.

[0342] In summary, the present application selects specific types and specific proportions of A elements and / or B elements to dope the phosphate positive electrode material, and adjusts the amount of oxalic acid and the types and amounts of vanadium source, phosphorus source, sodium source, fluorine source and carbon source, which is beneficial for the phosphate positive electrode material to have better electronic conductivity and structural stability, so that the compaction density and BET specific surface area of ​​the phosphate positive electrode material are significantly improved, thereby excellent in charge and discharge specific capacity, first coulomb efficiency, rate performance and cycle performance, which is beneficial to the preparation of high energy density sodium ion batteries.

[0343] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A phosphate positive electrode material, characterized in that: comprising a core and a carbon layer covering the core; The kernel expression is Na3V 2-x-y A x B y (PO4)2F3; Among them, 0≤x≤0.5, 0≤y≤0.5, x and y are not zero at the same time; The A element and the B element each independently include one or more of Fe, Mn, Ti, Al and Mg, and the A element and the B element are different from each other; The compaction density of the phosphate positive electrode material is ≥2.0g / cm 3 , BET specific surface area ≥8m 2 / g.

2. The phosphate positive electrode material according to claim 1, characterized in that One or more of the following conditions are met: (1) The mass fraction of the carbon layer in the phosphate positive electrode material is 1.8% to 3%; (2) The thickness of the carbon layer is 0.8 nm to 1.8 nm.

3. The phosphate positive electrode material according to claim 1, characterized in that: One or more of the following conditions are met: (1) The first charge specific capacity of the phosphate positive electrode material at 0.1C is ≥120 mAh / g; (2) The first discharge specific capacity of the phosphate positive electrode material at 0.1C is ≥110 mAh / g; (3) The first coulombic efficiency of the phosphate positive electrode material at 0.1C is ≥90%.

4. A method for preparing a phosphate positive electrode material, characterized in that: The following steps are involved: A vanadium source, oxalic acid, a phosphorus source, a dopant and a solvent are mixed and subjected to a reaction treatment to obtain a mixed solution; The mixed liquid is subjected to a first drying process and a first sintering process to obtain a precursor; The precursor, the sodium source, the fluorine source and the carbon source are mixed and ground to obtain a slurry; The slurry is subjected to a second drying process and a second sintering process to obtain the phosphate positive electrode material; The dopant includes a first source and / or a second source, the first metal element in the first source and the second metal element in the second source each independently include one or more of Fe, Mn, Ti, Al and Mg, and the first metal element and the second metal element are different from each other.

5. The method for preparing a phosphate positive electrode material according to claim 4, characterized in that: The step of mixing a vanadium source, oxalic acid, a phosphorus source, a dopant and a solvent, and subjecting the mixture to a reaction treatment to obtain a mixed solution comprises: The vanadium source and the solvent are mixed at a first temperature for a first time to obtain a first solution; The first solution, the dopant and the oxalic acid are mixed at a second temperature for a second time to obtain a second solution; The second solution and the phosphorus source are mixed at a third temperature for a third time to obtain the mixed solution; Wherein, the first temperature is 80°C to 90°C, and the first time is 30min to 90min; The second temperature is 90°C to 95°C, and the second time is 30min to 60min; The third temperature is 90° C. to 100° C., and the third time is 12 min to 36 min.

6. The method for preparing a phosphate positive electrode material according to claim 5, characterized in that: One or more of the following conditions are met: (1) When the dopant includes the first source and the second source, the molar ratio of the vanadium element in the vanadium source, the oxalic acid, the phosphorus element in the phosphorus source, the first metal element in the first source, and the second metal element in the second source is (0.9-1.1): (2.5-3.5): 1: (0-0.25): (0-0.25); (2) the vanadium source comprises one or more of vanadium pentoxide, vanadium trioxide, vanadium dioxide, ammonium metavanadate, sodium metavanadate, sodium orthovanadate and vanadyl oxalate; (3) the phosphorus source comprises one or more of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate and sodium phosphate; (4) the first source includes one or more of an oxide, a hydroxide and a salt compound containing the first metal element; (5) The second source includes one or more of oxides, hydroxides and salt compounds containing the second metal element.

7. The method for preparing a phosphate positive electrode material according to any one of claims 4 to 6, characterized in that: One or more of the following conditions are met: (1) the molar ratio of the phosphorus element in the precursor, the sodium element in the sodium source, the fluorine element in the fluorine source, and the carbon element in the carbon source is 1:(1.3-1.5):(1.3-1.5):(0.48-0.9); (2) the sodium source comprises one or more of sodium fluoride, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium phosphate; (3) The fluorine source includes one or more of sodium fluoride, ammonium fluoride and hydrogen fluoride; (4) The carbon source includes one or more of glucose, polyethylene glycol, sucrose and ascorbic acid.

8. The method for preparing a phosphate positive electrode material according to any one of claims 4 to 6, characterized in that: One or more of the following conditions are met: (1) The sintering temperature of the first sintering treatment is 700° C. to 750° C., and the holding time is 1 h to 3 h; (2) The sintering temperature of the second sintering treatment is 550° C. to 750° C., and the holding time is 8 h to 12 h.

9. A positive electrode sheet, characterized in that: The invention comprises the phosphate positive electrode material according to any one of claims 1 to 3, or comprises the phosphate positive electrode material prepared by the preparation method of the phosphate positive electrode material according to any one of claims 4 to 8.

10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.